An extension of a Ger’s result - Marinescu, Dan Ştefan; Monea, Mihai (Annales Mathematicae Silesianae, 2017)
The aim of this paper is to extend a result presented by Roman Ger during the 15th International Conference on Functional Equations and Inequalities. First, we present some necessary and sufficient conditions for a continuous function to be convex. We will use these to extend Ger’s result. Finally, we make some connections with other mathematical notions, as g-convex dominated function or Bregman distance.